Modeling Business Process Improvement (BPI) Distribution Flow at PT. DWI PUTRA MANUNGGAL using the Business Process Model and Notation (BPMN) Approach: Modeliing Business Process Improvment (BPI) Alur Distribusi pada PT. DWI PUTRA MANUNGGAL dengan Pendekatan Business Process Model and Notation (BPMN) - Primasari, Bela Dwi; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
A company must maintain the stability of its business processes. To ensure smooth business operations, one approach is to enhance competitive quality for consumers. Maintaining consumer trust can be achieved by ensuring the stability of quality products and fast service. This study was conducted at PT. Dwi Putra Manunggal, located in Malang Regency, East Java. The company faces inefficiencies in its distribution process, causing delays in getting products to consumers. To improve business processes, an analysis using the Business Process Improvement (BPI) method can be performed. BPI is used to find solutions to ongoing business process issues. To evaluate and implement improvements, modeling notation written in Business Process Model and Notation (BPMN) can be used, providing stakeholders with an overview of the business process improvements made. By using BPMN notation, the actual (as-is) and recommended (to-be) business process simulations and models can be identified. As a result, PT. Dwi Putra Manunggal's business processes need improvement through BPI, with several parts of the business process requiring simplification. The simplification, simulated and modeled using BPMN, results in a minimum time of 7 hours, a maximum time of 13 hours, and an average time of 13 hours and 10 minutes.A company must maintain the stability of its business processes. To ensure smooth business operations, one approach is to enhance competitive quality for consumers. Maintaining consumer trust can be achieved by ensuring the stability of quality products and fast service. This study was conducted at PT. Dwi Putra Manunggal, located in Malang Regency, East Java. The company faces inefficiencies in its distribution process, causing delays in getting products to consumers. To improve business processes, an analysis using the Business Process Improvement (BPI) method can be performed. BPI is used to find solutions to ongoing business process issues. To evaluate and implement improvements, modeling notation written in Business Process Model and Notation (BPMN) can be used, providing stakeholders with an overview of the business process improvements made. By using BPMN notation, the actual (as-is) and recommended (to-be) business process simulations and models can be identified. As a result, PT. Dwi Putra Manunggal's business processes need improvement through BPI, with several parts of the business process requiring simplification. The simplification, simulated and modeled using BPMN, results in a minimum time of 7 hours, a maximum time of 13 hours, and an average time of 13 hours and 10 minutes. Keywords: BPI, BPMN, Modeling and Simulation, Distribution